Pediatric Chronic Kidney Disease: Mind the Gap Between Reality and Expectations - Chien-Ning Hsu; Pei-Chen Lu; Wei-Ting Liao; You-Lin Tain (Children)
Pediatric chronic kidney disease (CKD) is a growing concern that often originates early in life, yet significant challenges remain in translating clinical guidelines into real-world practice. World Kidney Day 2025 highlights the importance of early detection, but the three levels of preventive strategies commonly recommended for adults may not be directly applicable to children. Unlike adult CKD, primary prevention in pediatrics should focus on prenatal, neonatal, and early-life factors such as congenital anomalies of the kidney and urinary tract (CAKUT), preterm birth, maternal health, and environmental exposures. Secondary prevention, involving early detection through screening, is crucial, yet the effectiveness of mass urinary screening in children remains a subject of global debate. Several key challenges persist, including the accurate estimation of glomerular filtration rate (eGFR), consistent definition and diagnosis of pediatric hypertension, identification of reliable biomarkers, and targeted screening in specific pediatric populations. Although clear guidelines exist to manage CKD progression and enhance quality of life, a critical gap remains between what is known and what is practiced. Closing this gap requires robust evidence to inform best practices, improve health-related quality of life, and advance pediatric kidney replacement therapies. To protect and improve kidney health for every child worldwide, these challenges must be acknowledged, and sustainable, evidence-based solutions must be developed and implemented without further delay.